Contribution of Lecturers Attributes in Distance Education Accounting Science in Higher Education - Hanny, Hanny; Dewi , Nunik Lestari; Setiana, Sinta; Crystalin, Aura Regia (Jurnal Akuntansi, 2024)
Abstract Purpose - This study aimed to investigate the impact of lecturer personal attributes (APD) on the relationship between Distance Learning/Distance Education (PJJ) and Accounting learning effectiveness (EPA) in higher education. The uniqueness of the study was the collection of primary data over a year into the pandemic (2021), with the expectation that APD would be more favorable and homogeneous compared to data collected in 2020. Design/methodology/approach - The sample comprised 353 accounting studentsexperiencing PJJ from a campus equipped with a Learning Management System (LMS), selected using Purposive Sampling method. Furthermore, the hypotheses were tested using Moderated Regression Analysis (MRA). Findings - The results showed that PJJ had a significantly positive effect on EPA in higher education, while lecturers APD did not strengthen the influence of PJJ on EPA.Research limitations/implications – But interestingly this research found that personal attributes of lecturers (APD) were identified as an independent variable influencing EPA. Keywords: Lecturers Personal Attributes, Distance Education, Accounting, and Higher Education